An Analysis of the Symbol in Westlife's Song Lyrics - Rosita, Hanna Eka; Purwanto, Bambang; Rosyidi, Mohamad Ikhwan (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2019)
Song is one example of literature. Listening song is enjoyable activity, but the listener cannot get a pleasure if they do not understand the meaning in the song. Sometimes song consists of symbol to describe the meaning of a song. Based on the reason, it brought the researcher to find out the symbol and meaning in the song lyrics and to explain the impacts of symbol toward real life. This study applied a descriptive qualitative method. Through this method the researcher tried to analyze, explain, and find out the meaning of the symbols by using Charles Sanders Pierce’s theory. In this case, Charles Sanders Pierce developed a triadic model in illustrating the definition of the sign as a symbol. The triadic model consisted of three components; representamen, object and interpretant. The unit analysis of this study were Westlife’s songs, there were more than 145 songs in 11 albums. Because of the large amount of the songs, the researcher chose 7 songs from the Greatest Album of Westlife that are Swear it Again, If I Let You Go, Flying without Wings, I Have a Dream, My Love, Uptown Girl, and You Raise Me Up. This study contained 5 kinds of symbols that were symbol of color (12 items), symbol of thing (19 items), symbol of situation (18 items), symbol of sound (5 items), and symbol of imaginative (7 items). Furthermore, the most dominant symbol was symbol of thing. Symbols brought some impacts to real life to help the listeners or the readers to understand the real meaning toward real life. Keywords: Symbol, song, semiotics, westlife